Review: Allee effects in social species. (6th November 2017) - Angulo, Elena; Luque, Gloria M.; Gregory, Stephen D.; Wenzel, John W.; Bessa‐Gomes, Carmen; Berec, Ludek; Courchamp, Franck
Abstract: Allee effects have important implications for many aspects of basic and applied ecology. The benefits of aggregation of conspecific individuals are central to Allee effects, which have led to the widely held assumption that social species are more prone to Allee effects. Robust evidence for this assumption, however, remains rare. Furthermore, previous research on Allee effects has failed to adequately address the consequences of the different levels of organisation within social species' populations. Here, we review available evidence of Allee effects and model the role of demographic and behavioural factors that may combine to dampen or strengthen Allee effects in social species. We use examples across various species with contrasting social structure, including carnivores, bats, primates and eusocial insects. Building on this, we provide a conceptual framework that allows for the integration of different Allee effects in social species. Social species are characterised by nested levels of organisation. The benefits of cooperation, measured by mean individual fitness, can be observed at both the population and group levels, giving rise to "population level" and "group level" Allee effects respectively. We also speculate on the possibility of a third level, reporting per capita benefits for different individuals within a group (e.g. castes in social insects). We show that group size heterogeneity and intergroup interactions affect the strength of population‐level demographic Allee effects. Populations with higher group size heterogeneity and in which individual social groups cooperate demonstrate the weakest Allee effects and may thus provide an explanation for why extinctions due to Allee effects are rare in social species. More adequately accounting for Allee effects in social species will improve our understanding of the ecological and evolutionary implications of cooperation in social species. Abstract : In social species, individuals form groups to optimise their fitness. When group size is small, extinctions are more likely, a demographic process called Allee effect. The authors review evidence for Allee effects in different taxa and they model the role of demographic and behavioural factors that may combine to strengthen Allee effects.